Guidance for studies evaluating the accuracy of rapid tuberculosis drug-susceptibility tests - Georghiou, Sophia B.; Denkinger, Claudia M. (The journal of infectious diseases, 2019)
Abstract. The development and implementation of rapid molecular diagnostics for tuberculosis (TB) drug-susceptibility testing is critical to inform treatment o
Published: 08 October 2019
Gesehen am 05.11.2019